META-NET Strategic Research Agenda for Multilingual Europe 2020 - Georg Rehm (White Paper Series, 2013)
In everyday communication, Europe's citizens, business partners and politicians are inevitably confronted with language barriers. Language technology has the potential to overcome these barriers and to provide innovative interfaces to technologies and knowledge. This document presents a Strategic Research Agenda for Multilingual Europe 2020. The agenda was prepared by META-NET, a European Network of Excellence. META-NET consists of 60 research centres in 34 countries, who cooperate with stakeholders from economy, government agencies, research organisations, non-governmental organisations, language communities and European universities. META-NET's vision is high-quality language technology for all European languages.